2021
DOI: 10.1016/j.clnesp.2021.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of eating behavior during COVID-19 lockdown: Longitudinal analyses of 22,374 adults

Abstract: Background & Aims The COVID-19 pandemic has led to the implementation of stay-at-home and lockdown measures. It is currently unknown if the experience of lockdown leads to long term changes in individual’s eating behaviors. The objectives of this study were: i) to derive longitudinal trajectories of change in eating during UK lockdown, and ii) to identify risk factors associated with eating behavior trajectories. Method Data from 22,374 UK adults from the UCL COVID-19 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
108
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(130 citation statements)
references
References 39 publications
(45 reference statements)
13
108
1
8
Order By: Relevance
“…This could well be attributed to “comfort eating”, i.e. eating induced by negative affect [ 49 ] as also supported by a large population based study [ 50 ] whereby individuals with depressive symptoms were more likely to report a change in eating habits.…”
Section: Discussionmentioning
confidence: 89%
“…This could well be attributed to “comfort eating”, i.e. eating induced by negative affect [ 49 ] as also supported by a large population based study [ 50 ] whereby individuals with depressive symptoms were more likely to report a change in eating habits.…”
Section: Discussionmentioning
confidence: 89%
“…Data from a large study of 22,374 UK adults found that one third reported changes to quantities of food consumed through the first lockdown period. Subgroups of the population were found to persistently eat more, whilst others reported eating less (particularly those who were already underweight; Herle, Smith, Bu, Steptoe, & Fancourt, 2021). Another study found that 56% of participants reported snacking more frequently (Robinson et al, 2021).…”
Section: Eating Behaviour and Nutritionmentioning
confidence: 99%
“…A recent study indicated that people have consumed on average one portion of fruit and vegetables less per day than before the pandemic (Naughton et al, 2021). A potential mechanism for changes to eating behaviours may be emotion dysregulation, with those reporting changes to their eating behaviours during the pandemic also displaying greater levels of depression (Herle et al, 2021; McAtamney et al, 2021). Barriers to weight management have, for example, included reports of lower motivation to eat healthily and lower control over eating (Robinson et al, 2021).…”
Section: Eating Behaviour and Nutritionmentioning
confidence: 99%
“…Some studies find women increasing exercise more than men [58], being less likely to alter their alcohol intake [55] and being more likely to increase fruit and vegetables intake, eat less or partake in healthy eating [8,21,58]. However, UK women have also been shown to eat both more and less during the pandemic [18]. Greater COVID-19-related stress was reported in females during the start of the pandemic, but psychological distress tended to return to pre-pandemic levels by mid-2020 [59,60].…”
Section: Discussionmentioning
confidence: 99%